Evolution and Adaptation of the Avian H7N9 Virus into the Human Host - Bisset, Andrew T. (Microorganisms, 2020)
Influenza viruses arise from animal reservoirs, and have the potential to cause pandemics. In 2013, low pathogenic novel avian influenza A(H7N9) viruses emerged in China, resulting from the reassortment of avian-origin viruses. Following evolutionary changes, highly pathogenic strains of avian influenza A(H7N9) viruses emerged in late 2016. Changes in pathogenicity and virulence of H7N9 viruses have been linked to potential mutations in the viral glycoproteins hemagglutinin (HA) and neuraminidase (NA), as well as the viral polymerase basic protein 2 (PB2). Recognizing that effective viral transmission of the influenza A virus (IAV) between humans requires efficient attachment to the upper respiratory tract and replication through the viral polymerase complex, experimental evidence demonstrates the potential H7N9 has for increased binding affinity and replication, following specific amino acid substitutions in HA and PB2. Additionally, the deletion of extended amino acid sequences in the NA stalk length was shown to produce a significant increase in pathogenicity in mice. Research shows that significant changes in transmissibility, pathogenicity and virulence are possible after one or a few amino acid substitutions. This review aims to summarise key findings from that research. To date, all strains of H7N9 viruses remain restricted to avian reservoirs, with no evidence of sustained human-to-human transmission, although mutations in specific viral proteins reveal the efficacy with which these viruses could evolve into a highly virulent and infectious, human-to-human transmitted virus.